Subsidence history, crustal structure, and evolution of the Somaliland-Yemen conjugate margin - Ali, M; Watts, A (Blackwell Publishing Ltd, 2013)
We have used biostratigraphic data from deep exploration wells to determine the tectonic subsidence history of the Somaliland (northwestern Somalia)-Yemen conjugate margin, a poorly known margin in the central part of the Gulf of Aden. Bathymetry and magnetic anomaly data suggest the Gulf of Aden is a young feature that formed following the rifting apart and breakup of the African and Arabian plates ~32 Ma. Our tectonic subsidence data suggest, however, that the present-day Gulf of Aden developed on an earlier Mesozoic rift system. The oldest episode of rifting initiated at ~156 Ma and lasted for ~10 Ma and had a NW-SE trend. We interpret the rift as a late stage event associated with the breakup of Gondwana and the separation of Africa and Madagascar. At ~80 Ma, there is evidence of an intermediate rift event which correlates with a rapid increase in spreading rate on the ridges separating the African and Indian and African and Antarctica plates and a contemporaneous slowing down of Africa's plate motion. The combined effect of all three rifting events has been to thin the crust and upper mantle by up to a factor of 2. The amount of thinning deduced from the wells is in accord with the crustal structure inferred from available seismic refraction data and process-oriented gravity and flexure modeling. The margin is asymmetric with a steeper gradient in the Moho on the Yemen side than the Somaliland side. The main discrepancy is on the Yemen side where the gravity-derived Moho is 10 km deeper than the well-derived Moho. We attribute the discrepancy to the addition of material at the base of the crust since rifting, possibly magma sourced from the Afar plume. Keypoints Backstripped subsidence data can be explained by a multirift modelCrustal structure shows a steeper Moho at the Somaliland marginThe Yemen margin is underplated, perhaps by magmatic material © 2013. American Geophysical Union. All Rights Reserved.